Puberty: rebellion and growing — how are scenarios in traditional pre-puberty and puberty dynamics still present? - Todorović, Milorad V. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
Great instability in the roles, wide fluidity in the theater of love, which is contrary with stable world of yesterday, can not be transferred or impact on children growing up in space of fluid love. Parents who were given the right to determine the kind of pleasure and imposing a form of love to the children entries the confusion eliminating of those clear standards that were present in earlier periods. Pathological manifestations, especially of girls in the pre-puberty and puberty, which was reported on the psychotherapies undertaken because of the difficulty in adapting and education, can provide insights into normal processes such as are difficult to obtain with direct observation. Understanding any phase or any level within phase of development implies a clear insight into the history of the previous phases and level of the structure built by then. Even when it comes to revolutionary changes or about flurry in development process that is actually about amplifying evolutionary process. The theoretical problem with puberty, as a phase that can be defined as new edition of the infantile period, is that it comes after a period of so-called latency is illogical that after the (apparently) peaceful development can reach such large, revolutionary changes. It seems that even the development theory has not paid the necessary attention to something that could be defined as preparatory activities from which puberty depends. It is clear that this is the one invisible dynamics present in the psyche is in this quiet, pre-puberty period.